Secondary stroke prevention in patients with patent foramen ovale. Issue 5 (September 2021) - Rhoades, Ruben; Tzeng, Diana; Ruggiero, Nicholas
Abstract : Purpose of review: Although a patent foramen ovale (PFO) is an established risk factor for cryptogenic ischemic stroke, strategies for secondary prevention remain controversial. Increasing evidence over the past decade from well designed clinical trials supports transcatheter PFO closure for selected patients whose stroke was likely attributable to the PFO. However, patient selection using imaging findings, clinical scoring systems, and in some cases, thrombophilia testing, is crucial for determining patients most likely to benefit from closure, anticoagulation, or antiplatelet therapy. Recent findings: Recent studies have found that patients with a high Risk of Paradoxical Embolism (RoPE) score and those with a thrombophilia benefit more from closure than medical therapy (including antiplatelet or anticoagulant therapy) alone. Meta-analyses have demonstrated an increased short-term risk of atrial fibrillation in closure patients, and that residual shunt after closure predicts stroke recurrence. Last, recent data have been inconclusive as to whether patients receiving medical therapy only benefit more from anticoagulation or antiplatelet therapy, so this remains an area of controversy. Summary: Transcatheter PFO closure is an evidence-based, guideline-supported therapy for secondary stroke prevention in patients with a PFO and cryptogenic stroke. However, proper patient selection is critical to achieve benefit, and recent studies have helped clarify those patients most likely to benefit from closure.